(untitled) (Classica Cracoviensia, 2015)
Intellectual Sources of Historian’s Legitimization - The Case of Gregory of Tours The question of Gregory’s of Tours awareness of the persuasive potential of his learning he demonstrates in his works is discussed. The Touronian bishop’s high evaluation of the erudition of other men is clearly shown and juxtaposed with his opinion concerning his linguistic competence. Gregory’s ability to embellish his style, being a sign of the literary training is demonstrated. His degree of acquaintance with the classical literature is assessed and his familiarity with Latin poetry is underlined. The literal meaning of his statements concerning classical literature as detrimental to a Christian soul is contrasted with the subtle and indirect play those statements engage his readers in; their implicit meaning is shown to contradict their direct significance. Various examples of Gregory’s efforts to display his erudition in the field of literature and his high degree of learning, including a fair number of erudite digressions are brought forth. Gregory’s unambiguous statement concerning the intention with which he inserted them into his text is evoked. Finally, the Touronian Bishop’s positive judgment about his audience’s capacity of properly evaluating the erudite content of his writing is demonstrated and corroborated with the external evidence provided by contemporary sources.